Hacking events: Project development practices and technology use at hackathons. (December 2019) - Richterich, Annika
Hackathons are techno-creative events during which participants get together in a physical location. They may be hosted by civic communities, corporations or public institutions. Working individually or in teams, usually for several days, participants develop projects such as hardware or software prototypes. Based on a digital ethnography of two events in the Netherlands and Denmark, this article investigates project development practices at hackathons. In particular, it analyses how participants organized their project work and which technologies were used in support of their creative endeavours. Hackathons are increasingly competitive rather than collaborative events, involving time pressure, inducements such as prizes, and requiring efficient skills utilization. I argue that this facilitates the following tendencies: Firstly, strategic effort is put into final presentations. Projects need to be convincingly presented, and persuasively pitching an idea becomes crucial. Secondly, there is only limited time for personal learning, since participants' existing skills need to be efficiently applied if a team wants to stay competitive. This encourages division of labour within groups: a tendency which seems especially problematic given that IT skills biases are often expressed in terms of gender. Thirdly, participants are more inclined to use technologies that are proprietary but appear 'open enough'. In light of this observation and by drawing on the concept of technology as resource and opportunity, I discuss the techno-political implications of utilized technologies. With this analysis, I aim at contributing to the critical debate on hackathons as productive but likewise ideologically significant fields of 'hacking cultures'.